Structural and Kinetics Understanding of Support Effects in Pd-Catalyzed Semi-Hydrogenation of Acetylene. (January 2021) - Cao, Yueqiang; Ge, Xiaohu; Li, Yurou; Si, Rui; Sui, Zhijun; Zhou, Jinghong; Duan, Xuezhi; Zhou, Xinggui
Abstract: In this study, the support effects on the Pd-catalyzed semi-hydrogenation of acetylene have been investigated from the structural and kinetic perspectives. According to the results of kinetic analysis and X-ray photoelectron spectroscopy, hydrogen temperature-programmed reduction, temperature-programmed hydride decomposition, and in situ X-ray diffraction measurements, using carbon nanotubes as support for Pd nanocatalysts with various sizes instead of α-Al2 O3 decreases the Pd 0 3d binding energy and suppresses the formation of undesirable palladium hydride species, thus increasing the ethylene yield. Furthermore, X-ray absorption spectroscopy, high-resolution transmission electron microscopy, and C2 H4 temperature-programmed desorption studies combined with density-functional theory calculations reveal the existence of a unique Pd local environment, containing subsurface carbon atoms, that produces positive geometric effects on the acetylene conversion reaction. Therefore, tailoring the Pd local environment and electronic properties represents an effective strategy for the fabrication and design of highly active and selective Pd semi-hydrogenation catalysts.